Distinct Root Microbial Communities in Nature Farming Rice Harbor Bacterial Strains With Plant Growth-Promoting Traits - Sinong, Grace Flavyeliz; Yasuda, Michiko; Nara, Yoshiyuki; Lee, Chol Gyu; Dastogeer, Khondoker Mohammad Golam; Tabuchi, Hiroyasu; Nakai, Hirokazu; Djedidi, Salem; Okazaki, Shin (Frontiers in Sustainable Food Systems, 2021)
A nature farming system is an ecological farming practice that entails cultivating crops without using chemical fertilizers and pesticides. To understand the diversity and functions of root microbiomes associated with nature farming systems, we compared the root microbial community of rice under nature farming conditions with those under conventional farming conditions. High-throughput amplicon analysis demonstrated a higher abundance and greater diversity of the root microbiome under unfertilized nature farming conditions than under conventional conditions. The application of chemical fertilizers reduced the microbial diversity and abundance of some beneficial taxa important for plant growth and health. Subsequently, we isolated and identified 46 endo- and epiphytic bacteria from rice roots grown under nature farming conditions and examined their plant growth-promoting activity. Six potential isolates were selected for plant growth assessment in insoluble P- and K-containing media. Most of the isolates promoted rice growth, and Pseudomonas koreensis AEPR1 was able to enhance rice growth significantly in both insoluble P- and K-containing media. Our data indicated that nature farming systems create a distinct root microbiome that is comparatively more diverse and supports plant growth under low-input cultivation practices than under conventional practices. The potential isolates could be exploited as sources with potential applications in sustainable agriculture.